1981
DOI: 10.1021/bi00526a009
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of tropoelastin production and elastin messenger ribonucleic acid activity in developing sheep lung

Abstract: During fetal development of the sheep lung, elastin content continually increases. For examination of the processes controlling this elastin accumulation, an explant culture system was characterized with respect to changes in tropoelastin production in sheep lung during fetal and early postnatal development. Relative tropoelastin production in cultured lung explants, quantitated by immunoprecipitation, was about 0.3% of total [14C] valine incorporation during the period from 55 to 104 days after conception. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…With respect to lung, the observations to date (11,33,42) suggest that chick aorta and lung tropoelastin are nearly identical in size and have similar chemical properties and composition (Table 1). There also appear to be close similarities between sheep nuchal ligament and sheep lung elastin (15,41).…”
Section: Components Of Elastic Fiber: Isolation and Composition Of Elmentioning
confidence: 75%
See 3 more Smart Citations
“…With respect to lung, the observations to date (11,33,42) suggest that chick aorta and lung tropoelastin are nearly identical in size and have similar chemical properties and composition (Table 1). There also appear to be close similarities between sheep nuchal ligament and sheep lung elastin (15,41).…”
Section: Components Of Elastic Fiber: Isolation and Composition Of Elmentioning
confidence: 75%
“…Later investigations, however, were unable to confirm the presence of soluble proelastin greater than 76,000-78,000 daltons (11,15,16,41,(46)(47)(48)(49). When translation systems are used utilizing messenger RNA preparations from aortae and lung, the major elastinlike products of translation appear to resemble tropoelastin with perhaps a short extension peptide (2,15,16,41,42,48,49 (34,35). Protocol IV, based on cyanogen bromide cleavage, is useful when it is certain that the elastin to be isolated contains no methionyl residues (5,32).…”
Section: Components Of Elastic Fiber: Isolation and Composition Of Elmentioning
confidence: 94%
See 2 more Smart Citations
“…The increase in TE synthesis by RPF was dose-response curve was similar to the mRNA changes, with the a specific, developmentally regulated event that cannot be totally maximum at lo-' to M with no differences between 7-d related to the overall increase in the protein synthesis because the magnitude of increase in TE production was greater than that for total protein. Signals for rapid decline of TE synthesis postnatally are unclear but developmental windows of the synthetic period have been described in various elastogenic cells/ tissues examined (18)(19)(20)(21)(22). Shibahara et al (22) have shown that in fetal sheep lung tissue, the period of rapid TE synthesis starts in the latter half of gestation, which is similar to bovine lung tissue (23) but distinct from rat lung, where elastin accumulation occurs mainly in the first 2 postnatal wk and becomes quiescent by 3 wk (1 1).…”
Section: 3mentioning
confidence: 99%